Diversity of Spa gene between methicillin-resistant and methicillin-sensitive Staphylococcus aureus bacteria in a tertiary referral hospital, Indonesia (Medical Journal of Indonesia, 2023)
BACKGROUND Spa typing is an effective and fast technique to identify the prevalence and spread of Staphylococcus aureus strains based on their spa gene profiles. The distribution of spa types will contribute to control the spread of S. aureus. Little is known regarding the spa types of S. aureus in Indonesia. This study aimed to investigate the diversity of spa gene among S. aureus carriage isolates in North Sumatra Province, Indonesia. METHODS 79 S. aureus isolates consisting of 39 methicillin-resistant S. aureus (MRSA) and 40 methicillin-susceptible S. aureus (MSSA) carriage isolates were identified by VITEK2 Compact (Biomerieux, Indonesia) to detect mecA gene. All samples underwent spa typing and sequencing. RESULTS Spa gene was detected among 31/39 (79%) of the MRSA isolates and 24/40 (60%) of the MSSA isolates. Most spa typing genes were identified between 350 and 400 base pair (bp). t258 and t852 were the most prevalence spa types among MRSA and MSSA isolates, respectively. CONCLUSIONS Many MRSA and MSSA isolates encoded spa gene. The most genes detected were t258 and t852, identified in Germany and Portugal, respectively; while t18977 was initially identified in Malaysia. This indicated a global spread of MRSA according to spa typing.